Education Level and Teaching Experience as Determinants of Teacher Competence in Rural Islamic Primary Schools - Meriasih, Dewi; Madiistriyatno, Harries; Taufik, Kemal (JURNAL AL-TANZIM, 2026)
This study explores the simultaneous and partial associations among teachers’ educational level, teaching experience, and overall competence within a single rural Islamic primary school context. Using a quantitative survey design, the study involved a saturated sample of 30 teachers during the 2024/2025 academic year. Data were obtained from a validated teacher competence questionnaire and from institutional records on educational level and teaching experience. Descriptive statistics and multiple regression analyses were performed following standard assumption tests. The findings indicate that teachers’ education level and teaching experience are significantly associated with teacher competence, jointly accounting for 60.1% of the observed variance. Teaching experience shows a stronger association with competence than formal educational attainment, with incremental increases in competence scores observed across additional semesters of experience. While teachers holding a bachelor’s degree demonstrate higher competence scores than those without, these results should be interpreted with caution due to the study’s limited sample size and single-site design. Rather than offering broad generalizations, the findings provide context-specific insights that may inform future research and localized professional development initiatives in similar educational settings.